Fatigue resistance of welded steel tubular X-joints. (November 2020) - Papatheocharis, Theocharis; Sarvanis, Gregory C.; Perdikaris, Philip C.; Karamanos, Spyros A.; Zervaki, Anna D.
Abstract: High-cycle fatigue experiments are performed on welded tubular steel X-joints, with braces and chord of equal diameter. They are scaled-down joints, used extensively in offshore wind platforms. Three different welding procedures are considered in specimen fabrication: manual, fully-automatic and manual with HFMI post-weld treatment. Τwo possible locations for crack initiation were identified: chord "crown" and "in-between location", also verified by numerical calculations and fractography of failed specimens. Monotonic loading tests on fatigue-cracked specimens showed good performance in terms of ultimate strength and deformation capacity, despite the presence of through-thickness cracks. The results are compared with predictions from relevant design standards. Highlights: Fatigue tests are performed on tubular joints with β  = 1 and three weld procedures. Fatigue initiation sites are identified: chord "crown" and "in-between" points. Μonotonic-load tests are performed on fractured joints to determine their strength. Fractography verifies fatigue initiation sites and correlates with weld defects. Test results are compared with fatigue life predictions from relevant design codes.